An investigation on the impact of HIV/AIDS on the educators at King Williams Town schools – Eastern Cape, South Africa - Zisongile-Dekeda, Nosiphiwo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (M.Phil. (Industrial Psychology))--University of Stellenbosch, 2009.